1986
DOI: 10.1002/ppul.1950020406
|View full text |Cite
|
Sign up to set email alerts
|

Protective value of BCG vaccination in children in Bangkok, Thailand

Abstract: The protective effect of bacille Calmette-Guérin (BCG) vaccination against tuberculosis is controversial. In a study, 330 patients less than 12 years of age with tuberculosis, 52.1% of whom had had BCG vaccination, were compared with a control group of 1106 patients free of tuberculosis, 81% of whom had BCG vaccination. The occurrence of disseminated forms of tuberculosis, tuberculous meningitis, tuberculous peritonitis, and tuberculosis of bone and joints in BCG-vaccinated patients was quite low. With BCG vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Currently, BCG vaccination covers 85% of newborn infants, and it has been estimated that nearly 100 million children are vaccinated with BCG vaccine every year (12). Several studies have shown that BCG protects against TBM and that its efficacy is around 75 to 85% (8,18,27,34,105,129,163,188,194,212,244,248). Two recent meta-analyses also concluded that BCG vaccination protects against TBM (39,175).…”
Section: Preventionmentioning
confidence: 99%
“…Currently, BCG vaccination covers 85% of newborn infants, and it has been estimated that nearly 100 million children are vaccinated with BCG vaccine every year (12). Several studies have shown that BCG protects against TBM and that its efficacy is around 75 to 85% (8,18,27,34,105,129,163,188,194,212,244,248). Two recent meta-analyses also concluded that BCG vaccination protects against TBM (39,175).…”
Section: Preventionmentioning
confidence: 99%
“…Thailand has included mass immunization with the BCG vaccine for every newborn as the national public health policy since 1970. In Thailand, 76% of the protective effect of BCG against TB has been previously demonstrated, and a significantly lower extrapulmonary TB rate compared to pulmonary TB has also been demonstrated (Chavalittamrong et al, 1986). However, clear evidence of BCG vaccine efficacy against TB and extrapulmonary TB by experimental study is still required.…”
Section: Treatments and Management Of Tbmmentioning
confidence: 99%
“…For instance, in the Thai population, the most predominant ages of TBM patients are 31-45 years (35.3%), and only 12% of TBM patients are less than 15 years old (Yorsangsukkamol et al, 2009). With BCG vaccination, a significantly lower incidence of disseminated TB, such as TBM, was found in patients less than 12 years old compared to pulmonary TB (Chavalittamrong et al, 1986). The average ages of TBM patients in particular regions, even on different continents, are around 30 years higher (table 1).…”
Section: Predisposing Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have a positive history of tuberculosis in the family, though they may be free of tuberculosis. It is known that vaccination against tuberculosis does not ensure 100% protection [4].…”
Section: Lower-lung-field Tuberculosis In Saudi Arabiamentioning
confidence: 99%